Gemtuzumab Ozogamicin Treatment Results in Decreased Proliferation and Differentiation of Human Megakaryocytes but Does Not Inhibit Mature Platelet Function. (October 2022) - Vitsky, Allison; Sacaan, Aida; Hu, Wenyue; Finkelstein, Martin; Reagan, William
Mylotarg (Gemtuzumab ozogamicin [GO]), an antibody drug conjugate comprising a CD33-directed antibody linked to calicheamicin, is approved for use in certain acute myeloid leukemia patients. Following reports of prolonged thrombocytopenia and hemorrhagic events in a subset of patients, a detailed series of in vitro and ex vivo studies was performed at the request of regulators, both to look at the effects of GO on platelet production and to determine whether treatment with GO was likely to affect platelet aggregation under a variety of conditions. Treatment with GO resulted in cellular cytotoxicity and/or decreased differentiation during human megakaryocyte development. However, GO did not impair platelet aggregation under the experimental conditions evaluated. Ultimately, the effect of GO on megakaryocyte development observed in our studies was determined to have no impact on the risk-benefit assessment in the intended patient population, as thrombocytopenia is a known side effect of GO, and monitoring of platelet counts in patients is already strongly recommended.